HUBUNGAN TINGKAT PENGETAHUAN TENTANG ABORSI DENGAN SIKAP REMAJA PUTRI TERHADAP SEKS PRANIKAH DI KELAS XII SMAN KUTOWINAGUN - Wahanani, Evi; Aminoto, Cokro; Utami, Wuri (LPPM STIKES MUHAMMADIYAH GOMBONG, 2012)
Nowadays Promiscuity or free sex among teenagers is becoming a trend. sexual behavior without enough knowledge and unstable good level of emotion can cause problems such as abortion. This study aimed to find out the correlation between knowledge about abortion and female teenagers’ attitude about Premarital Sex in Grade XI IS of MAN Kutowingangun in 2012. This correlation study used cross sectional approach. Data were analyzed by using frequency distributions and bivariate analyzes using the test statistic Contingency Coefficient. The results showed that 92.7% of the respondents had good knowledge about abortion, 97.6% had good attitudes toward premarital sex. Those indicated that there is a correlation between knowledge about abortion and female teenagers’ attitude about Premarital Sex in Grade XI IS of MAN Kutowingangun in 2012 with the value of p = 0.008 (<0.05). Keywords : attitudes, abortion, knowledge, premarital sex, female teenagers